Replacement of fish meal with crustacean meals in diets for long-snouted seahorse, hippocampus guttulatus: digestibility and growth performance - Palma, Jorge (2024)
This study investigated the effect of partially replacing fish meal with krill and copepod meals in inert diets co-fed with shrimp on the growth and nutrient digestibility of long-snout seahorses (Hippocampus guttulatus). A control diet (Diet 1) using raw starch and four experimental diets with similar protein (approximate to 44.8%) and energy (approximate to 15.1 MJ/kg) levels were tested. Diet 2 used fish meal as the sole protein source, while in Diets 3-5, krill and copepod meals replaced 44% of the fish meal. Seahorses fed shrimp + Diets 2-5 showed significantly higher growth rates (p < 0.05) than those fed shrimp + Diet 1, though there were no significant growth differences among Diets 2-5. Digestibility of dry matter (46.1% to 72.2%), lipids (73.3% to 85.5%), crude protein (89.8% to 95.8%), energy (82% to 92.2%), and phosphorus (28.7% to 64.4%) varied with diet, being consistently lower in seahorses fed shrimp + Diet 1. As an agastric species, H. guttulatus did not exhibit impaired digestibility for any of the tested nutrients, minerals, or energy. This study suggests that crustacean meals can effectively substitute fish meal in inert diets for this species, contributing to the sustainability and optimization of captive seahorse husbandry practices.